Langerhans cell histiocytosis – the role of radiation therapy - Ziółkowska, Ewa; Wiśniewski, Tomasz; Indrak-Rawicka, Katarzyna; Windorbska, Wiesława (Contemporary Oncology/Współczesna Onkologia, 2011)
Langerhans cell histiocytosis is a rare illness and its ethiology is unknown. About 1200 new morbidity is registered in the USA annually. Langerhans cell histiocytosis has a wide range of signs and differential prognosis. Bones are the most common localization of disease (40-78%). Nowadays histiocytosis hasn’t got clinical trials and standard of treatment. Surgery is the treatment of choice in limited form of histiocytosis, but in diffuse form the chemotherapy is always used. The role of radiation therapy in histiocytosis is unknown. The most of researchers recommends the radiotherapy in following conditions: reccurence or progresion of disease, spinal cord compression, bone pain or bone’s break threat, exophthalmus, non-surgical local changes. The aim of this study is the review of literature about using radiation therapy in treatment of Langerhans cell histiocytosis.